The phenolic and flavonoid content and biological activity of Curcuma (Curcuma xanthorrhiza) fractions with different solvent polarities. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to identify the impact of variations in solvent polarity on the solubility of secondary metabolite compounds, which were correlated as antioxidant and antibacterial agents for Escherichia coli (ATCC 11725), Salmonella sp. (ATCC 22504), Staphylococcus aureus (ATCC 11526), and Bacillus subtilis (ATCC 11626). Materials and Methods: A total of 500 gm of Temulawak flour (Curcuma xanthorrhiza) was macerated gradually using the step gradient polarity (SGP) technique, where the solvents (methanol, ethyl acetate, and n-hexane) used had different levels of polarity. The extracting process of secondary metabolite components of Temulawak flour began with the use of non-polar solvents, semipolar solvents, and polar solvents, respectively. Each soaking process was completed for 5 × 24 h. Results: From the Temulawak extract with different levels of solvent polarity, 76.048 gm were obtained for the methanol fraction, 106.242 gm for the ethyl acetate fraction, and 154.575 gm for the n-hexane fraction. The results of the antioxidant activity test showed that the ethyl acetate fraction had the highest inhibitory value for antioxidant activity of 50% (IC50) 22.59 mg/l. The results of this research’s β-carotene content were 0.0865 gm. Ethyl acetate fraction was known to have good activity from the antibacterial activity test. The inhibition zone of E. coli and B. subtilis bacteria was 11.5 ± 0.71 with a minimum concentration of 3.13 mg/ml. The inhibition zone of S. aureus was 10.5 ± 0.17 with a minimum inhibitory concentration (MIC) of 6.25 mg/ml, while the inhibition zone for Salmonella sp. was 8.125 ± 0.35 with a MIC of 37.50 mg/ml. Conclusion: All fractions have moderate antibacterial activity, yet the ability of the ethyl acetate fraction of Temulawak extract was higher than the methanol and n-hexane fractions.J. Adv. Vet. Anim. Res., 12(1): 192–204, March 2025http://doi.org/10.5455/javar.2025.l886